Detection of thermal radiation using lanthanum-strontium-iron oxide (LSFO) bolometers - Wierzba, Pawel; Mazikowski, Adam; Kosmowski, Bogdan B. (Photonics Letters of Poland, 2009)
Non-stoichiometric lanthanum-strontium-iron oxides (LSFO) are a promising class of materials for bolometers due to relatively high emissivity in the mid-IR and high temperature coefficient of resistance. We report, for the first time to the authors’ knowledge, detection of the thermal radiation emitted by a blackbody calibration source whose temperature was 38°C (311 K) by an LSFO bolometer placed 500 mm from the source. Signal-to-noise ratio (SNR) of about 62 (i.e. 35.9 dB) was achieved using vector averaging of acquired spectra and by an increase in the measurement time. In the Letter we estimate the accuracy of temperature measurement and outline the directions of further research.